The Documentation Strategy and Archival Appraisal Principles: A Different Perspective - Cox, Richard J. (Archivaria, 1994)
North American archivists have recently witnessed an upsurge in writings about appraisal theory. This essay takes a different approach to this topic. It attempts to describe a set of basid principles, derived from the archival literature, that relate to the practice of appraising records. These principles bridge the gap between theory and practice, but they represent–in the author’s view–something more than just methodology. The essay also seeks to relate the decade-old discussion to the archival documentation strategy, showing how the strategy both emanates from such principles and is consistent with them. RÉSUMÉ Les archivistes nord-américains ont récemment été témoins d’une recrudescence des écrits concernant la théorie de l’évaluation archivistique. Le présent article adopte une approche différente de ce sujet: il tente de décrire une série de principes fondamentaux tirés de la littérature archivistique concernant l’exercice de l’évaluation des dossiers. Ces principes font le lien entre la théorie et la pratique, mais ils représentent, selon l’auteur, quelque chose de plus qu’une simple méthodologie. L’article tente également d’évoquer la discussion vieille d’une décennie sur la stratégie de documentation archivistique, en démontrant que cette stratégie émane à la fois de tels principes et qu’elle est compatible avec ces principes.